2017
DOI: 10.1080/14992027.2017.1417644
|View full text |Cite
|
Sign up to set email alerts
|

Clinical trials, ototoxicity grading scales and the audiologist’s role in therapeutic decision making

Abstract: The audiologist's role in therapeutic decision making goes beyond collection of the audiogram. Clear communication to stakeholders in ototoxicity monitoring is paramount, and toxicity grading scales are one tool to facilitate this exchange. Various factors should be considered in advance of selecting the most appropriate scale to capture hearing loss, and no scale is without limitation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Otherwise, any change in hearing may be misrepresented as being related to ototoxicity caused by treatment when it may be conductive in nature. 27,28 When testing children less than 7 months of age, it is necessary to do so using a 1-kHz probe tone. Literature has shown that this probe tone frequency is more sensitive to middle ear dysfunction in neonates and infants (up to 6 months of age) compared with a 226-Hz probe tone.…”
Section: Immittance Testingmentioning
confidence: 99%
See 4 more Smart Citations
“…Otherwise, any change in hearing may be misrepresented as being related to ototoxicity caused by treatment when it may be conductive in nature. 27,28 When testing children less than 7 months of age, it is necessary to do so using a 1-kHz probe tone. Literature has shown that this probe tone frequency is more sensitive to middle ear dysfunction in neonates and infants (up to 6 months of age) compared with a 226-Hz probe tone.…”
Section: Immittance Testingmentioning
confidence: 99%
“…But it is also important to convey to the physician the impact the hearing loss is having on the patient's communication ability. 27 The ASHA guidelines define a significant change in hearing compared with baseline as follows:…”
Section: What Constitutes a Significant Change And The Use Of Gradingmentioning
confidence: 99%
See 3 more Smart Citations